Compact tag antenna for UHF active RFID applications. Issue 7 (9th January 2017) - Lu, Jui-Han; Liou, Zi-Hao
Abstract : By introducing an L-shaped metal plate connecting with the spiral monopole antenna, a planar compact ultra-high-frequency (UHF) tag antenna for radiofrequency identification system is proposed. With the overall antenna size of only 13 × 9 × 1.6 mm 3, the proposed tag antenna provides the measured impedance bandwidth of 12 MHz to comply with Taiwan UHF operating band (922–928 MHz). The measured peak gain and antenna efficiency are approximately −1.1 dBi and 27% for Taiwan UHF band, respectively. Meanwhile, the measured reading distance can approach 250 m. Good tag sensitivity is obtained across the desired frequency band.